Increased Gastric Retention Capacity, Assessed by Scintigraphy, after APC Treatment of Dilated Gastrojejunal Anastomosis - Barrichello, Sérgio (2018)
Background: Weight regain occurs in about 20% of patients after Roux-en-Y gastric bypass (RYGB). Studies have reported that in most cases this regain is associated with dilatation of the gastrojejunal anastomosis. To correct this dilatation, one of the methods used is the application of argon plasma coagulation (APC). Case: The authors report the case of a 39-year-old woman submitted to RYGB who had weight regain. In the endoscopic evaluation, the patient presented with dilatation of the gastrojejunal anastomosis, for which treatment with APC and an adjusted diet was proposed. After 3 sessions of APC, the patient presented with a reduction of the anastomosis diameter, weight loss, and increased satiety to food, with an increased gastric emptying time evidenced by scintigraphy. Conclusion: APC proved to be a safe and efficacious method.